2019
DOI: 10.1101/509182
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mammalian Amoeboid Swimming is propelled by molecular and not protrusion-based paddling in Lymphocytes

Abstract: Mammalian cells developed two main migration modes. The slow mesenchymatous mode, like fibroblasts crawling, relies on maturation of adhesion complexes and actin fiber traction, while the fast amoeboid mode, observed exclusively for leukocytes and cancer cells, is characterized by weak adhesion, highly dynamic cell shapes, and ubiquitous motility on 2D and in 3D solid matrix. In both cases, interactions with the substrate by adhesion or friction are widely accepted as a prerequisite for mammalian cell motility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 63 publications
3
11
0
Order By: Relevance
“…Repeatedly, adhesive steering was attributed to a tug of war between rival parts of the leading edge, those parts that have the strongest grip on the substrate being expected to win. In contrast, the migration of amoeboid cells, and in particular leukocytes, can take place without adhesive contact with a matrix (24) and even without a matrix (27). Directed motion controlled by adhesion is therefore not conceptually straightforward for amoeboid cells, and indeed, adhesive haptotaxis of leukocytes has, to our knowledge, never been evidenced.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Repeatedly, adhesive steering was attributed to a tug of war between rival parts of the leading edge, those parts that have the strongest grip on the substrate being expected to win. In contrast, the migration of amoeboid cells, and in particular leukocytes, can take place without adhesive contact with a matrix (24) and even without a matrix (27). Directed motion controlled by adhesion is therefore not conceptually straightforward for amoeboid cells, and indeed, adhesive haptotaxis of leukocytes has, to our knowledge, never been evidenced.…”
Section: Discussionmentioning
confidence: 92%
“…On alternated stripes of adhesion contrast 100% (Figure 2-B and middle panel of movie 1 and 2), cells travelled both on and across adherent and non-adherent stripes. T lymphocytes are indeed able to crawl on adhesive substrates and swim on anti-adhesive substrates (27). However, portions of path with lengths of tens of micrometers appeared with a steady orientation in the direction of stripes ( Figure 2-B), and orientation bias appears clearly on rose plots in the direction of stripes, with an anisotropy index of 0.5 ± 0.1 for both ICAM-1 and VCAM-1 substrates.…”
Section: T Cells Haptotax On Substrates With Adherent and Non-adherenmentioning
confidence: 96%
“…Gradient devices have been used to study the chemotaxis of different cells such as bacteria, neutrophils, T lymphocytes, dendritic, endothelial and cancer cells 2 3 4 5 6 7 . We recently described a new migration mode on immune cells termed swimming, where cells move in a non-adherent, non-confined environment 8 . This lack of adhesion makes swimming cells very sensitive to fluid flow.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies [26,27,28,29,30] have reported that several eukaryotic cells such as neutrophils, T-lymphocytes and microorganisms such as Dictyostelium amoeba can exhibit shape deformation based pure swimming away from the substrate instead of conventional adhesion assisted crawling on the substrate and display comparable swimming speed (as fast as crawling). This corroborates the observed fact that leukocytes can move in extracellular matrix despite the inactivity of the principal adhesion molecules (integrins) [29].…”
Section: Introductionmentioning
confidence: 99%